Architectural Fantasies on Classical Antiquity in the Renaissance Drawings - Efimova, Elena A. (Actual Problems of Theory and History of Art, 2015)
The author of the article investigates the problem of perception of ancient architectural monuments in the Renaissance artistic culture. She considers a curious phenomenon — long-term existence and wide spreading of pictured imaginary monuments and “pseudo-antique” fantasies embodied in the so-called “Roma antica” architectural drawings and engravings, along with contemporaneous works that render images of authentic Roman antiquities. The author ascertains their long-term expansion and consistent evolution within a century from the late 15th to the late 16th century in Italy and abroad, and its strong influence on the visual arts: painting, sculpture, and decorative arts. She analyses various versions of the origin of these fantasies, their relationship with the humanistic literary-philosophical tradition and professional craft practice. The author suggests that motifs of the authentic 1st century AD Roman painting and actual archaeological experience of the Renaissance artists were possibly reflected in these fantasies. She expresses her opinion on the impact they have had on formation of the genres like architectural landscape with ruins, grotesque décor, and architecture of minor forms in landscape art, as well as upon theoretical studies and projects of the Renaissance architects. It can be thus concluded that two kinds of perception coexisted in the Renaissance concept of Classical antiquity: on the one hand, accurate render of true archaeological sites, and, on the other hand, their fictional arbitrary reconstructions based on creative transformation of historical and artistic experience. It reveals an important specific feature of the epoch’s thinking. Rather than being distant, abstract ideal construct and an object of scholarly research, Classical antiquity was live and relevant material, which used to be in a constant dialogue with the contemporary art process. The awareness of the historical distance between different eras did not presuppose the gap between them — Classical antiquity continued to be “restored” in accordance with the Renaissance creative goals. This creative attitude towards antiquity distinguishes the Renaissance from all subsequent cultures.